UNBOXING ENTREPRENEURSHIP: ENHANCING YOUR PRICING STRATEGY KNOWLEDGE - Simatupang, Apriani; Hutabarat, Moses. L. P.; Arianto, Radityo; Gea, Fikra Wini; Kereh, Regina Ferosali Majesty (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
In an increasingly competitive business environment, understanding pricing strategy has become one of the key elements for entrepreneurial success. The Community Service Program (PkM) titled "Unboxing Entrepreneurship: Enhancing Your Pricing Strategy Knowledge", organized by Universitas Pelita Harapan, aimed to provide fundamental insights into pricing strategies for students of SMA Tarsisius 2 and SMA Tritunggal Semarang. The activity involved expert speakers in business strategy and student entrepreneurs who shared their practical experiences. Through theoretical sessions, case studies, and interactive simulations, participants were trained to analyze costs, understand the market, and strategically determine product prices. The outcomes of the program demonstrated improved student comprehension of the importance of pricing in business, along with enhanced practical skills in analyzing and setting competitive prices. Furthermore, the program successfully inspired students to develop entrepreneurial ideas based on a more structured strategy, enabling them to face market challenges with greater confidence.